Structure and Optical Properties of CdS Thin Films after Hard Ultraviolet Irradiation - Dobrozhan, A. I.; Meriuts, A. V.; Kopach, G. I.; Mygushchenko, R. P.; Kropachek, О. Y. (Institute of Electrical and Electronics Engineers, 2019)
The influence of hard ultraviolet radiation on the crystalline structure and optical properties of thin-film semiconductor cadmium sulfide layers obtained by the method of non-pulsed direct current magnetron sputtering was investigated. It was established that for hexagonal modification cadmium sulfide films after hard UV irradiation with a quantum energy of 10.5 eV for 10 hours the lattice parameter c changes from 6.77(01) Å to 6.78(88) Å. The results of the study of the optical properties of cadmium sulfide films before and after hard ultraviolet irradiation indicate that the transmission coefficient, reflection coefficient, refraction coefficient and band gap do not change.
Keywords: cadmium sulfide; non-pulsed direct current magnetron sputtering; hard ultraviolet; thin films